Intestinal antibody pattern of coeliac disease: association with gamma/delta T cell receptor expression by intraepithelial lymphocytes, and other indices of potential coeliac disease. Issue 4 (April 1994) - Arranz, E; Bode, J; Kingstone, K; Ferguson, A
Abstract : Patients with coeliac disease have IgM antibodies and IgA anti-gliadin antibody in gut secretions, and also high counts of intraepithelial lymphocytes (IEL) that express the gamma/delta T cell receptor. These features of intestinal immunity may be markers of latent coeliac disease. Their occurrence was examined in 77 patients referred for jejunal biopsy, in whom biopsy histology was normal, to establish the extent to which these, and other candidate markers (high total IEL count, serum IgA anti-gliadin antibody (AGA), and increased permeability) coexist in the same patient. Twelve patients had high serum anti-gliadin antibody titres and nine increased permeability. The gamma/delta IEL count was high (> 5.5 per mm villus epithelium) in nine patients, the intestinal antibody pattern was positive in 21, and the total IEL count was high (> 40 per 100 enterocytes) in 13. Overall, 31 patients had positive indices, but in 19 only a single test was abnormal. High gamma/delta IEL counts were found in six of 21 intestinal antibody positive patients, but in only two of 56 who were intestinal antibody negative (p < 0.001); there were no other significant associations. Clinical tests of gluten sensitivity will be required to establish the prevalence of latent gluten sensitive enteropathy in the 40% of patients referred for jejunal biopsy in whom one or more of the immunological indices of potential coeliac disease is present.